(untitled) (Experimental biology, 2017)
mTOR (mammalian target of rapamycin) is an important hub kinase of growth factor and nutrient signaling. Functioning as a part of two distinct multiprotein complexes - mTORC1 and mTORC2 (mTOR complexes 1 and 2) – it regulates cell growth and proliferation. We have established that Gly-934 residue of mTORC2’s rictor plays a key role in maintaining rictor-Sin1 interaction.